Comparison of Wound Infection And Hospital Stay Between Primary Closure And Delayed Primary Closure In Patients With Perforated Appendicitis (Medical Forum Monthly, 2024)
Objective: To compare the outcomes of primary closure and delayed primary closure in term of wound infection and hospital stay in patients treated perforated appendicitis. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Department of General Surgery, Bhatti International Teaching Hospital and Central Park Hospital, Lahore from September 2017 to August 2018. Materials and Methods: Eighty patients of both genders with ages >15 years with clinical suspicion of perforated appendicitis which was later confirmed peroperatively were included in this study after written consent. Patients were randomly divided into two groups and were scheduled for conventional appendectomy. Group I consist of 40 patients in which wound was closed primarily at the time of surgery. Group II consist of 40 patients and underwent delayed primary closure on 3rd post-operative day. Outcomes such as wound infection and hospital stay were analyzed. Results: In Group I 21 (52.5%) were males and 19 (47.5%) were females with mean age 35.21±9.80 years while in Group B 23 (57.5%) were males and 42.5% were females with mean age 36.25+10.45 years. Wound infection was found in 18(22.5%) patients. 14 patients in Group-Ias compared to 4 patients in Group II (delayed primary closure). Patients with primary closure had less hospital stay as compared to patients with delayed primary closure 5.35+1.02 vs 7.65±1.15 days p-value 0.002. Conclusion: Patients treated with primary closure had high rate of wound infection as compared to delayed primary closure and patients with primary closure had less hospital stay as compared to patients with delayed primary closure.